The The Relationship Between Individual Characteristics and The Number Of Children on Drug Waste Management Behavior at The Household Scale in Kedaton District of Bandar Lampung - Indika Poloriani Tunang (Fakultas Kedokteran Universitas Lampung, 2025)
Background: Medicines are often stored in households for health-related needs. However, prolonged storage can lead to an increase in pharmaceutical waste. This type of waste requires specific handling through proper management behavior. Within the household context, mothers play a vital role in managing pharmaceutical waste. The aim of this study is to examine the relationship between individual factors such as age, education level, type of occupation, income, and number of children with the behavior of housewives in managing pharmaceutical waste in the Kedaton District. Method: This research is an analytical observational study using a cross-sectional design and purposive sampling technique. A total of 108 housewives in Kedaton District were selected as the research sample. Data were collected using a questionnaire and analyzed using the chi-square test. Results: It was found that 43 respondents (39.8%) demonstrated poor pharmaceutical waste management behavior, while 65 individuals (60.2%) showed good management behavior. Statistical analysis revealed significant relationships between age, education level, occupation, and income with pharmaceutical waste management behavior. However, no significant relationship was found between the number of children and this behavior. Conclusion: Most housewives in Kedaton District have shown positive behavior in managing pharmaceutical waste. Factors such as age, education, occupation, and income influence this behavior, whereas the number of children does not have a significant impact. Keywords: Individual Characteristics, Management Behavior, Number of Children, Pharmaceutical Waste, Household.